The art of sim-making: What to learn from film-making - Fatimah Lateef; Brad Peckler; Eric Saindon; Shruti Chandra; Indrani Sardesai; Mohamed Alwi Abdul Rahman; S Vimal Krishnan; Afrah Abdul Wahid Ali; Rose V Goncalves; Sagar Galwankar (Journal of Emergencies, Trauma and Shock, 2022)
The components of each stage have similarities as well as differences, which make each unique in its own right. As the film-making and the movie industry may have much we can learn from, some of these will be covered under the different sections of the paper, for example, “Writing Powerful Narratives,” depiction of emotional elements, specific industry-driven developments as well as the “cultural considerations” in both. For medical simulation and simulation-based education, the corresponding stages are as follows: Development Preproduction Production Postproduction and Distribution. The art of sim-making has many similarities to that of film-making. In fact, there is potentially much to be learnt from the film-making process in cinematography and storytelling. Both film-making and sim-making can be seen from the artistic perspective as starting with a large piece of blank, white sheet of paper, which will need to be colored by the “artists” and personnel involved; in the former, to come up with the film and for the latter, to engage learners and ensure learning takes place, which is then translated into action for patients in the actual clinical care areas. Both entities have to go through a series of systematic stages. For film-making, the stages are as follows: Identification of problems and needs analysis Setting objectives, based on educational strategies Implementation of the simulation activity Debriefing and evaluation, as well as Fine-tuning for future use and archiving of scenarios/cases.